2021
DOI: 10.5194/bg-18-1893-2021
|View full text |Cite
|
Sign up to set email alerts
|

Review and syntheses: Impacts of turbidity flows on deep-sea benthic communities

Abstract: Abstract. Turbidity flows – underwater avalanches – are large-scale physical disturbances that are believed to have profound and lasting impacts on benthic communities in the deep sea, with hypothesized effects on both productivity and diversity. In this review we summarize the physical characteristics of turbidity flows and the mechanisms by which they influence deep-sea benthic communities, both as an immediate pulse-type disturbance and through longer-term press-type impacts. Further, we use data from turbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 122 publications
(281 reference statements)
0
3
0
Order By: Relevance
“…One of the key factors also having an effect on the structure of bottom communities in the trenches is the environmental instability of, in particular, bottom sediments. Oceanic trenches are located in zones of seismic activity which often cause landslides and turbidity flows in areas of steep slopes of trenches, which negatively affects bottom communities (Jumars and Hessler, 1976;Belyaev, 1989;Oguri et al, 2013;Bigham et al, 2021). In one of the samples from maximum depths of the Kuril-Kamchatka Trench, we found a small amount of silt characteristic of trench floor sediments and a rolled lump of very dense clay of approximately 0.5 m in diameter, which occupied almost the entire volume of the box corer.…”
Section: The Hadal Zone Of the Kuril-kamchatka Trenchmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key factors also having an effect on the structure of bottom communities in the trenches is the environmental instability of, in particular, bottom sediments. Oceanic trenches are located in zones of seismic activity which often cause landslides and turbidity flows in areas of steep slopes of trenches, which negatively affects bottom communities (Jumars and Hessler, 1976;Belyaev, 1989;Oguri et al, 2013;Bigham et al, 2021). In one of the samples from maximum depths of the Kuril-Kamchatka Trench, we found a small amount of silt characteristic of trench floor sediments and a rolled lump of very dense clay of approximately 0.5 m in diameter, which occupied almost the entire volume of the box corer.…”
Section: The Hadal Zone Of the Kuril-kamchatka Trenchmentioning
confidence: 99%
“…Landslides and turbidity flows can have catastrophic consequences for bottom communities, up to mass mortality of animals on large areas of the trench floor (Belyaev, 1989). Moreover, landslides and turbidity flows cause habitat heterogeneity in trenches and canyons, which affects the diversity and abundance of bottom macrofauna (Belyaev, 1989;Bigham et al, 2021). It is very likely that the differences in the taxonomic composition and abundance of macrofauna at the deepest stations A11 and A7 are associated with the differences in the local habitat conditions for animals living on the trench floor.…”
Section: The Hadal Zone Of the Kuril-kamchatka Trenchmentioning
confidence: 99%
“…Itou et al, 2000). Within this strategy, a focus should be given to capturing large events, such as mass wasting following earthquakes, rather than simply examining the after-effects (Oguri et al, 2013;Bao et al, 2018;Kioka et al, 2019a), that might be rare but have extensive implications for biological succession, trophic coupling and element cycling (Bigham et al, 1893;Heezen et al, 1955). A long-term sampling strategy will simultaneously be essential for developing a baseline for identifying and tracking the impacts of global change.…”
Section: Recommendations For the Future Of Hadal Sciencementioning
confidence: 99%
“…Location along the flow path, time since disturbance, and the specific metrics of productivity measured all make it difficult to directly compare this study to previous studies on communities impacted by turbidity flows. But the trends seen in megafauna invertebrates in Kaikōura Canyon following the turbidity flow for abundances (increase/stay the same) and biomass (variable; Astropectinidae: increase, B. filiformis: stay the same, Macroudidae: decrease) are opposite of the overall trend for all fauna size classes from previous turbidity flow studies (generally negative for abundance, but positive for biomass; Chapter 1; Bigham et al, 2021). For the megafauna, there have only been three other studies on abundances at turbidites, two in the Venezuela Basin which found decreased abundances (Richardson et al, 1985;Briggs et al, 1996) and one in the Madeira Abyssal Plain which found increased abundances (Thurston et al, 1994); all three studies observed increased biomass.…”
Section: Impact Of the Turbidity Flow On Benthic Productivitymentioning
confidence: 82%
“…There are many types of disturbance in the marine environment, biological (e.g., Reidenauer and Thistle, 1981;Thrush et al, 1991;Hall, 1994;Preen, 1996), physical (e.g., Hall, 1994;Aller, 1997;Rosenberg et al, 2002), and anthropogenic (e.g., bottom trawling, Kaiser, 1998) that influence benthic communities across a range of spatial scales. One of the largest and potentially the most pervasive and persistent natural physical disturbances in the marine environment are caused by turbidity flows (see Section 1.3 in Chapter 1 for details, Bigham et al, 2021).…”
Section: Introductionmentioning
confidence: 99%